Pertumbuhan vegetatif dan generative tanaman lidah buaya (aloe vera L.) varietas chinensis pada pasir pantai - Ihza Nurrudin Yahya; Renannti Lunnadiyah Aprilia (Fakultas Pertanian Universitas Majalengka, 2025)
Aloe vera (Aloe vera L.) is a plant belonging to the Liliaceae family, characterized by thick, fleshy leaves that are long, tapering at the tips, green in color, and contain a mucilaginous gel. Aloe vera cultivation can be conducted in coastal sandy soil. However, one of the major challenges of coastal sandy soil is abiotic stress caused by salinity. The propagation source significantly influences both generative and vegetative growth of the plant. This study aims to determine the optimal combination of propagation source and salinity stress for improving the generative and vegetative growth of Aloe vera in coastal sandy soil. The research was conducted in Tegalretno Village, Petanahan District, Kebumen Regency, Central Java, Indonesia. Cultivation took place inside a greenhouse measuring 21m x 10m. The plants were grown in 40 cm polybags, with a 50 cm spacing between each plant. A total of 252 plants were used in the study. The experiment followed a factorial Completely Randomized Design (CRD) with two factors. Data were analyzed using SPSS at a 5% significance level. The results demonstrated that the interaction between propagation source and salinity levels in coastal sandy soil significantly influenced both vegetative and generative growth of Aloe vera. The best vegetative growth was observed in the combination of propagation source from Gunung Kidul with an additional 10 g/L salinity (A1C2), producing an average plant height of 67.125 cm. Meanwhile, the highest number of shoots (3.69 shoots per week) was obtained in the combination of propagation source from Cilacap with an additional 10 g/L salinity (A3C2). Keyword : Lidah buaya, pasir pantai